A combined fuzzy approach to determine the best region for a nuclear power plant in Turkey - Erdogan, Melike; Kaya, Ihsan (ELSEVIER, 2016)
When increase in energy needs of developing countries cannot be met by conventional energy sources, alternative energy sources are considered to substitute them. Nuclear energy that meets the needs of a greater proportion of energy demands for countries is one of effective alternative energy types. In this context, after deciding on the use of nuclear energy, the selection of the most suitable location for the production of nuclear power is one of the important decision making problems. In this paper, we performed a facility location selection model for Turkey in meeting the needs of energy with using new and unused source of nuclear energy. For this aim, a combined fuzzy multi criteria decision making (MCDM) methodology that consists of Interval type-2 fuzzy analytical hierarchy process (AHP) that is applied to determine weights of criteria and interval type-2 fuzzy TOPSIS that is applied for ranking alternatives is used to determine the best location alternative for the nuclear power plant. By the way, the obtained results have been analyzed depending upon the criteria that used for the evaluation process. The obtained results are compared with existing nuclear power plants location selection policy for Turkey and some suggestions have been made for the plants where would be the located are not decided. By the way, a sensitivity analysis has been conducted to analyze effects of changes in decision's parameters. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Multi criteria decision making; Nuclear power plant location; Interval type-2 fuzzy numbers; AHP; TOPSIS; DECISION-MAKING METHODOLOGY; SITE SELECTION; LOCATION; SETS; Computer Science